Financial implications of RHD genotyping of pregnant women with a serologic weak D phenotype. Issue 9 (21st March 2015) - Kacker, Seema; Vassallo, Ralph; Keller, Margaret A.; Westhoff, Connie M.; Frick, Kevin D.; Sandler, S. Gerald; Tobian, Aaron A.R.
Abstract : BACKGROUND: Hemolytic disease of the fetus and newborn, classically caused by maternal–fetal incompatibility of the Rh blood group D antigen, can be prevented by RhIG prophylaxis. While prophylactic practices for pregnant women with serologic weak D phenotypes vary widely, RHD genotyping could provide clear guidance for management. This analysis evaluated the financial implications of using RHD genotyping to guide RhIG prophylaxis among pregnant females. STUDY DESIGN AND METHODS: A Markov‐based model was constructed to evaluate the costs of RHD genotyping for pregnant females with serologic weak D phenotypes to inform RhIG prophylaxis. Using a comparison strategy of managing these women conservatively as D–, direct medical costs were assessed over 10‐ and 20‐year periods for a simulated population of US women. One‐way and probabilistic sensitivity analyses were used to assess the robustness of conclusions. RESULTS: Using base‐case variables, RHD genotyping for pregnant women with serologic weak D phenotypes is expected to marginally reduce overall costs. RHD genotyping these patients, rather than conservatively managing them as D–, would be cost‐saving when the cost of genotyping is below 256. Genotyping would decrease net costs among non‐Hispanic Caucasian females (–0.17/pregnancy), but would increase costs among non‐Hispanic African Americans (+0.51/pregnancy), non‐Hispanic American Indian/Alaskans (+0.10/pregnancy), and Hispanics (+0.37/pregnancy). Incorporating RHD genotyping would not significantly impact costs among Asians and Hawaiians/Pacific Islanders. CONCLUSIONS: Using RHD genotyping to guide RhIG prophylaxis among pregnant women with serologic weak D phenotypes may be clinically beneficial without increasing overall costs.